2018
DOI: 10.11646/zootaxa.4444.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Squalus clarkae sp. nov., a new dogfish shark from the Northwest Atlantic and Gulf of Mexico, with comments on the Squalus mitsukurii species complex

Abstract: Sharks of the genus Squalus have slow reproductive rates coupled with low genetic diversity, as is typical of deep-water sharks, making this group slow to rebound from depletion due to overfishing. The number of species within Squalus has been expanding recently due to increased attention on taxonomic revision, and a growing research focus on little-known deep-water sharks in general. Here we use genetics and morphology to describe a new species of dogfish shark, Squalus clarkae sp. nov. from the Gulf of Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 1 publication
2
19
0
Order By: Relevance
“…Additional specimens and samples were collected from bottom fish surveys from Maui to Lisianski Atoll, spanning nearly 2,000 km of the Hawaiian Archipelago. Because the 2010 genetic study showed extremely low diversity, we deemed 5–10 specimens adequate for taxonomic evaluation, a number on par with other revisions in this genus (Ward et al 2007; Pfleger et al 2018). To that end, five whole mature females and three whole mature male S.cf.mitsukurii from Oahu were retained as voucher specimens for morphometric and genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional specimens and samples were collected from bottom fish surveys from Maui to Lisianski Atoll, spanning nearly 2,000 km of the Hawaiian Archipelago. Because the 2010 genetic study showed extremely low diversity, we deemed 5–10 specimens adequate for taxonomic evaluation, a number on par with other revisions in this genus (Ward et al 2007; Pfleger et al 2018). To that end, five whole mature females and three whole mature male S.cf.mitsukurii from Oahu were retained as voucher specimens for morphometric and genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Recent years have shown that DNA sequencing in conjunction with morphological analyses is an effective approach for elucidating the alpha taxonomy of deep-water sharks (Avise 2004; Ward et al 2005; Last et al 2007c; Ebert et al 2010; Veríssimo et al 2014; Pfleger et al 2018). Findings from several studies have shown a mix of low genetic distances between well-established morphological species, and deep genetic splits between animals identified as conspecifics (Daly-Engel et al 2010; Veríssimo et al 2017; Daly-Engel et al 2018; Pfleger et al 2018; Daly-Engel et al submitted). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations